2017
DOI: 10.3389/fpls.2017.00235
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis and Identification of Differentially Expressed Genes in Strawberry after Preharvest Application of Benzothiadiazole and Chitosan

Abstract: The use of resistance inducers is a novel strategy to elicit defense responses in strawberry fruit to protect against preharvest and postharvest decay. However, the mechanisms behind the specific resistance inducers are not completely understood. Here, global transcriptional changes in strawberry fruit were investigated using RNA-Seq technology. Preharvest, benzothiadiazole (BTH) and chitosan were applied to the plant canopy, and the fruit were harvested at 6, 12, and 24 h post-treatment. Overall, 5,062 and 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 101 publications
3
59
0
Order By: Relevance
“…Interestingly, CAB‐binding proteins are specifically induced in grapevine genotypes resistant to P. viticola following pathogen inoculation and this could explain the effectiveness of CER against this pathogen observed in our experiments. Moreover, genes encoding CAB‐binding proteins are induced by SA treatment in Arabidopsis and by chitosan and benzothiadiazole in strawberry . These findings corroborate the hypothesis of the existence of crosstalk between defense and other signaling pathways, such as that regulated by the phytochrome A/red light, leading to the induction of CAB genes .…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, CAB‐binding proteins are specifically induced in grapevine genotypes resistant to P. viticola following pathogen inoculation and this could explain the effectiveness of CER against this pathogen observed in our experiments. Moreover, genes encoding CAB‐binding proteins are induced by SA treatment in Arabidopsis and by chitosan and benzothiadiazole in strawberry . These findings corroborate the hypothesis of the existence of crosstalk between defense and other signaling pathways, such as that regulated by the phytochrome A/red light, leading to the induction of CAB genes .…”
Section: Discussionmentioning
confidence: 69%
“…Proteins also play a role in building intracellular structure and energy generating reactions, such as mitochondrial electron transport (28). In a recent report, chitosan application at 1% (w/v) concentration was shown to trigger reprogramming of protein metabolism with an increase of storage proteins in Fragaria × annanasa (29). In another report, Anusuya and Sathiyabama (30) found that chitosan treatment at 0.1% (w/v) increased protein con-tent in Curcuma longa cv.…”
Section: Discussionmentioning
confidence: 99%
“…However, no visible necroses was observed in F. vesca plants upon spray treatment of chemicals or the mock treatment. Also, there are reports of spray treating strawberry plants with different chemicals to study induced resistance (Terry and Joyce, 2000;Eikemo, Stensvand and Tronsmo, 2003;Hukkanen et al, 2007;Landi et al, 2017;Saavedra et al, 2017). We therefore consider the observed effects to be the plant's induced responses to priming agent treatments.…”
Section: Discussionmentioning
confidence: 99%